PENGARUH METODE ICE BREAKING TERHADAP KEMAMPUAN KOGNITIF PESERTA DIDIK KELAS VIII PADA MATA PELAJARAN AKIDAH AKHLAK DI MTs NURUL FALAH SANGIANG KOTA TANGERANG - Nisa Hawariyah; Ahmad Haromaini; Ariesta Setyawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low cognitive abilities of eighth-grade students in the Aqidah Akhlak subject at MTs Nurul Falah Sangiang, Tangerang City, and the need to implement learning methods that create an active, engaging, and enjoyable classroom atmosphere. One instructional strategy considered effective is the ice breaking method, which consists of short, interactive activities designed to improve students' concentration, motivation, and readiness to participate in the learning process. This study aimed to determine the effect of the ice breaking method on students' cognitive abilities in the Aqidah Akhlak subject. This research employed a quantitative approach using a quasi-experimental method with a Pretest–Posttest Control Group Design. The sample consisted of 63 students, including 30 students in the experimental class, who received instruction using the ice breaking method, and 33 students in the control class, who were taught using conventional teaching methods. Data were collected through cognitive achievement tests administered as pretests and posttests. The data were analyzed using validity, reliability, normality, and homogeneity tests, followed by an Independent Samples t-test to examine the research hypothesis. The findings revealed a significance value (Sig.) of 0.030, which was lower than the significance level of 0.05. Therefore, the null hypothesis (H₀) was rejected and the alternative hypothesis (H₁) was accepted. Furthermore, the mean posttest score of the experimental class was 84.10, which was higher than that of the control class, 81.30. These results indicate that the implementation of the ice breaking method had a positive and statistically significant effect on students' cognitive abilities in the Aqidah Akhlak subject. Therefore, the ice breaking method can be considered an effective alternative instructional strategy for improving students' cognitive learning outcomes.